Simulation of the Effect of Cutting Angle in Lathe Process onDistribution of Cutting Temperature. (April 2020) - Ismail, T; Amrifan, SM; Irsyadi, Y; Riman, S; Rahmad, H
Abstract: Lathe machining process (turning) is one of the metal cutting operation is the most widely used. At the time of the cutting process almost all cutting energy is converted into heat through friction between furious with the chisel and the chisel with the workpiece, as well as the destruction molekulen or atomic bonding in the field of shear (shear plane). The heat produced will be distributed in workpiece surface, chisel eye, and furious. High cutting temperatures as a result of friction between the eyes chisel and workpiece, will have an impact on the wear rate of the active surface of the plastic deformation chisel and chisel. Cutting temperature can be measured in various ways, either directly or indirectly. However, in its application, direct measurement will find it difficult to reach the area of the cutting temperature. The difficulty is due to the relatively narrow measurement range, disturbance of movements machinery and hindered by furious that formed during the machining process is done. To overcome this we can do indirectly measuring process for measuring the temperature of the cutting. Indirect measurement can be done by simulation or modelling. This research uses Tungsten carbide as a cutting tool and AISI 4340 as the workpiece in the simulation process. FEM-simulation software used in this research is SolidWorks 2014 and Abaqus / CAE 6:14. Simulations were performed to analyze the influence of the temperature distribution of the corner cutting that occurs during cutting.